Dual solutions for heat and mass transfer in chemically reacting radiative non-Newtonian fluid with aligned magnetic field (Journal of Naval Architecture and Marine Engineering, 2017)
Through this paper we investigated the heat and mass transfer in chemically reacting radiative Casson fluid flow over a slandering/flat stretching sheet in a slip flow regime with aligned magnetic field. This study is carried out under the influence of non uniform heat source/sink. First we converted the governing equations of the flow into ordinary differential equations by making use of suitable similarity transformations. The obtained non-linear differential equations are solved numerically using Runge-Kutta based shooting technique. Further, graphical representation has been given to study the effects of various physical parameters on velocity, temperature and concentration fields. Also numerical computations has been carried out to investigate the influence of the physical parameters involved in the flow on skin friction, rate of heat and mass transfer coefficients. Through this investigation, it is observed that aligned angle, Casson parameter and velocity slip parameter have the tendency to control the velocity field. Also heat transfer rate in flat stretching sheet is higher than that of slendering stretching sheet. A good agreement of the present results with the existed literature has been observed.